Relapse Prevention for Managerial Training: A Model for Maintenance of Behavior Change - Marx, Robert D. (Academy of Management Review, 1982)
Although organizations invest heavily in training programs to enhance managerial effectiveness, little attention is paid to the transfer of such training from the workshop to the workplace. This paper describes a cognitive-behavioral model that offers a systematic approach to the maintenance of behavior. Relapse prevention strategies are discussed, and implications for management training and research are considered.